Plečnikova oprema župnijske cerkve sv. Cirila in Metoda za Bežigradom v Ljubljani - Lazarini, Franci (Acta historiae artis Slovenica, 2023)
The article discusses the furnishings of the parish church of Saints Cyril and Methodius in Ljubljana Bežigrad. The majority of the furnishings, including the high altar, communion rail, pulpit, chandeliers, organ case, sanctuary columns, the small altar of St. Joseph, the pillar of Our Lady, lamps and several smaller items (e.g. the frames for some of the paintings) were designed between 1934 and 1956 by Jože Plečnik, according to whose plans the church was also built. The role of commissioners, Bežigrad parish priests P. Kazimir Zakrajšek OFM, P. Gabrijel Planinšek OFM, P. Stanislav Marija Aljančič OFM and P. Krizolog Zajec OFM is also elucidated. Finally, the ultimate fate of the furnishings after 1957–1958 when the church was transferred to its current location is described.
Keywords: art commission; cerkvena oprema; church furnishings; Franciscans; frančiškani; Ljubljana (Slovenia); Parish church of Ss Cyril and Methodius; Plečnik, Jože; umetnostno naročništvo; Župnijska cerkev sv. Cirila in Metoda